Double posterior lateral plating arthrodesis for charcot ankle: A case series - Pradana, Ananto Satya (Ann Med Surg (Lond), 2021)
INTRODUCTION: Ankle arthrodesis is one of the managements for a significantly unstable Charcot ankle. Some of the methods of internal fixation for ankle arthrodesis include the use of intramedullary nails, screws, and plates. Ankle arthrodesis using intramedullary nails has become more popular. However, studies evaluating the use of plate fixation, particularly double posterior lateral plating, are limited. We report the clinical and radiological outcomes of double posterior lateral plating ankle arthrodesis in three diabetic Charcot ankle patients. PRESENTATION OF CASE: Three patients, aged 73, 67, and 65 years old, complained of ankle pain and with a history of type 2 diabetes mellitus. The physical examination revealed swelling and erythema without a sign of active infection. The radiological examination showed ankle deformity, and the American Orthopaedic Foot & Ankle Society (AOFAS) Ankle-Hindfoot scores were 5, 10, and 0, respectively. All patients were diagnosed with a diabetic Charcot ankle and underwent ankle arthrodesis using double posterior lateral plating. Four months and six months follow up revealed talus union, improved ankle deformity, and improved AOFAS Ankle-Hindfoot scores to 70, 76, and 73, respectively. DISCUSSION: Various methods of ankle arthrodesis are retrograde intramedullary nails, screws, and plates. In this report, we opt for plate fixation because it allows for stable internal fixation, adequate compression, high angular stability, and a lower irreversible deformation in osteoporotic bone. CONCLUSION: Double posterior lateral plating ankle arthrodesis provided satisfactory clinical and radiological outcomes. This method can be an alternative for patients with Charcot ankle requiring ankle arthrodesis.